Partisipasi Siswa Dalam Melestarikan Lingkungan Sekitar Sekolah Melalui Pembelajaran PJBL di SMPN 1 Rao Utara - Ernialis, Ernialis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to enhance student participation in preserving the school environment through the implementation of Project-Based Learning (PBL). The research was conducted in two cycles involving the creation of posters and videos as learning media to raise students' awareness of the importance of environmental conservation. The results show that in the first cycle, students began to understand the significance of environmental preservation, although challenges in message delivery and group collaboration remained. In the second cycle, the implementation of video creation allowed students to be more creative and improve their communication and collaboration skills. Overall, the project-based approach successfully increased student motivation and participation in maintaining the cleanliness and sustainability of the school environment.